Late Cretaceous and early Palaeocene Chalk Group sedimentation in the Greater Ekofisk area, North Sea central graben. - Kennedy, W (1987)
The study is based on an examination of cores and well-logs from 24 wells in the Greater Ekofisk area in the Norwegian sector of the North Sea central graben together with published data on these and other wells in the area. The depositional processes and facies recognized from core study are summarized, with emphasis on the distinction between pelagic autochthonous facies and allochthonous facies, notably slides, slumps, debris-flows and turbidites. These data are integrated into a formation-by-formation account of lateral and vertical changes in the Plenus Marl, Lower, Middle and Upper Hod, Tor, Lower and Upper Ekofisk formations across the area. Regional depositional models for Chalk group sedimentation are proposed. -J.M.H.